Habitação Evolutiva. Projeto para o Programa de Autoconstrução em Santa Maria da Feira - Ricardo Domingues Félix (2020)
This dissertation's main subject is housing. The right to proper housing has been, throughout the years, a recurring theme of debate at many levels (social, economical, political, and architectural). Due to this, multiple solutions and housing care programs have been created and implemented for the most needed populations. Within the extensive theme of housing, an opportunity arose to operate within an existing housing program. This housing care program is the "Programa de Autoconstrução" in Santa Maria da Feira municipality. It consists in providing support to solve housing shortage for low-income households living in the area, namely residents who, owning a vacant house or land, may want to recover or build their own houses. The practical side of this work will then be the consequence of a detailed theoretical study and will consist in the creation of a projectual methodology that best fulfi lls the premises of this program. Concepts and methodologies concerning social and lowbudget housing will be analyzed, starting with strategies of selfconstruction, incremental housing, and prefabrication with SIP panels. These strategies are assumed to give a better response to the contemporary housing needs and to the constant changes in household composition.